2018
DOI: 10.1017/s0029665118000101
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional strategies to prevent gastrointestinal toxicity during pelvic radiotherapy

Abstract: Radiotherapy-induced damage to non-cancerous gastrointestinal mucosa has effects on secretory and absorptive functions and can interfere with normal gastrointestinal physiology. Nutrient absorption and digestion may be compromised. Dietary manipulation is an attractive option with sound rationale for intervention. The aim of this review was to synthesise published evidence for the use of elemental formulae, low or modified fat diets, fibre, lactose restriction and probiotics, prebiotics and synbiotics to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 83 publications
(202 reference statements)
0
16
0
Order By: Relevance
“…Pelvic radiotherapy is associated with GI toxicity and deterioration of the nutritional status of patients [ 10 , 11 , 12 ]. We found that the PG-SGA score at the end of radiotherapy was associated with the PRO-CTCAE score but not physician-reported CTCAE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelvic radiotherapy is associated with GI toxicity and deterioration of the nutritional status of patients [ 10 , 11 , 12 ]. We found that the PG-SGA score at the end of radiotherapy was associated with the PRO-CTCAE score but not physician-reported CTCAE.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic radiotherapy is associated with gastrointestinal (GI) toxicities, including diarrhea, abdominal pain, food intolerance, and fecal incontinence [ 6 ]. GI toxicities are burdensome to patients, interfere with the quality of life, and can lead to nutritional status deterioration and muscle loss [ 7 , 8 , 9 , 10 , 11 , 12 ]. Muscle loss can, in turn, affect outcome and quality of life in women with gynecologic cancer [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elemental diet reduces pancreatic and biliary secretions that may aggravate radiotherapy-induced mucosal inflammation [92]. Many find it unpalatable and compliance with an elemental diet is generally poor, especially if started when most likely to be effective, before symptoms develop [93e96].…”
Section: Dietary Modifications During Pelvic Radiotherapymentioning
confidence: 99%
“…Pelvic radiotherapy causes damage to non-cancer gastrointestinal mucosa and has an effect on secretory and absorptive functions (51,52) . A review of dietary interventions to manage symptoms highlighted weak evidence for some dietary changes including elemental, low or modified fat and low lactose interventions (53) . The use of probiotics was more promising with four out of five studies suggesting that some symptoms benefit from their use although variations in the strength and strains and study methodologies make firm recommendations difficult.…”
Section: Nutrient Absorptionmentioning
confidence: 99%